Call of duty: the effects of phone calls on blood donor motivation. Issue 11 (14th July 2015) - Bruhin, Adrian; Goette, Lorenz; Roethlisberger, Adrian; Markovic, Alexander; Buchli, Regula; Frey, Beat M.
Abstract : BACKGROUND: Little is known about the long‐term effects of interventions aimed at increasing turnout among voluntary blood donors. STUDY DESIGN AND METHODS: We use a retrospective natural experiment with all 40, 653 donors who were repeatedly invited to blood drives in Zurich, Switzerland, between 2010 and 2013. The intervention is a quasi‐randomized phone call informing donors of a current shortage of their blood type. The panel structure of the data allows identification of different types of donors reacting to the phone call. RESULTS: Our analysis reveals two types. Type 1 donors make up 27.1% of the population. They are highly motivated and exhibit a baseline donation rate of 59.4% (p < 0.001). The phone call raises their probability to donate by 9.9% at the upcoming blood drive (p < 0.001). However, the phone call reduces their donation rate by 2.3% (p = 0.003) at each future blood drive. In contrast, the 72.9% of Type 2 donors exhibit a low baseline donation rate of 5.8% (p < 0.001). The phone call raises their probability to donate by 5.8% at the upcoming blood drive (p < 0.001). Moreover, the phone call leads to habit formation in Type 2 donors and increases their donation rate by 2.1% at the next blood drive (p = 0.03). CONCLUSION: Behavioral interventions are effective at increasing donation rates in the short run. However, they can crowd out the intrinsic motivation of the most motivated donors. Thus, blood donation services should avoid interventions for highly motivated donors and target them at irregular donors. Our results also sound a warning on using other interventions.